A Comparative Study between a Calcium Channel Blocker (Nicardipine) and a Combined Alpha-ß-Blocker (Labetalol) for the Control of Emergence Hypertension During Craniotomy for Tumor Surgery - Kross, R. (Institutional Knowledge at Singapore Management University, 2000)
We compared the efficacy of the combination of enalaprilat/labetalol with that of enalaprilat/nicardipine to prevent emergence postcraniotomy hypertension. A prospective, randomized open labeled clinical trial was designed to compare the incidence of breakthrough hypertension (systolic blood pressure [SBP] > 140 mm Hg) and adverse effects (hypotension, tachycardia, and bradycardia) between the two drug combinations. Secondarily, the effects of the drugs on SBP, mean blood pressure, and diastolic blood pressure were evaluated over the course of the study. Forty-two patients received enalaprilat 1.25 mg IV at dural closure followed by either multidose nicardipine 2 mg IV or labetalol 5 mg IV to maintain the SBP below 140 mm Hg. SBP was similarly controlled in both groups. There was a marginally smaller incidence of failures and adverse effects with labetalol. Blood pressure profiles were similar for both groups.